Oxidation: The Cornerstone of Carcinogenesis Oxidation and Tobacco Smoke Carcinogenesis. A Relationship Between Cause and Effect - Stavridis, John C.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
In order to learn oncology, it is necessary to acquire a comprehensive knowledge of molecular biology in carcinogenesis, and then, with this as a background, to consider the principles of the theoretical and clinical basis of the subject. For graduate students who are preparing themselves for the specialty of internal medicine or clinical oncology, and physicians who wish to become proficient in oncology, it is exceedingly difficult to be highly skilled and completely informed in this expanding field of science without a comprehensive text on the subject. This book is unique, due to its collective approach to the key aspects of the interdependency between three entities: oxidative stress, tobacco smoke and carcinogenesis, operating in a cause-effect sequence, in a concise and to the point manner. I hope this book will prove to be a helpful companion to the internist, the oncologist and the research scientist in molecular biology as well as a work of reference for the general practitioner and physician interested in cancer research.
Oxygen and Nitrogen Free Radicals -- Oxidative Stress -- Oxidative Damage of Genome DNA: Repair Mechanisms -- Mitochondria: Structure, Function and Relationship with Carcinogenesis -- Oxidative Activation of Transcription Factor Pathways by Cigarette Smoke Oxidants -- Cell Protection Mechanisms from Oxidation -- Role of DNA Adducts in Carcinogenesis -- Transmolecular Reactions of Genetic Toxicity: Alkylation and Methylation of DNA -- Toxicity and Carcinogenicity of Hydrocarbons -- Toxicity and Carcinogenicity of the Aromatic Hydrocarbons -- Toxicity and Carcinogenicity of Aldehydes -- Toxicity and Carcinogenicity of the Nitriles -- Toxicity and Carcinogenicity of the Eterocyclic Organic Compounds -- Toxicity and Carcinogenicity of Metals -- Oxidative Profile of Cigarette Smoke and Lung Cancer -- Smoking and Lung Cancer.
Keywords: MEDICINE; ONCOLOGY; HUMAN GENETICS; TOXICOLOGY; BIOMEDICINE; CANCER RESEARCH; ONCOLOGY; HUMAN GENETICS; MOLECULAR MEDICINE; PHARMACOLOGY/TOXICOLOGY.